Basic researchRole of nitric oxide in the plasma lipid profile in the rabbits - Sadeghi-Hashjin, Goudarz; Abuhosseini, Mohaddeseh; Asri-Rezaei, Siamak (Archives of Medical Science, 2009)
Introduction: One important aspect of endothelial function is synthesis and release of nitric oxide (NO), which is not only a potent vasodilator but also an inhibitor of the platelet aggregation and adhesion. It also suppresses the proliferation of vascular muscle cells and possesses a crucial role in the pathogenesis of several cardio-vascular diseases. The present study communicates adverse effects of mimicking endothelial dysfunction on the plasma lipid profile in vivo. Material and methods: Twenty five male rabbits were treated s.c. twice daily for 7 successive days with either saline solution, nitroglycerin (NTG, 0.1 mg/kg), L-arginine (10 mg/kg), Nw-nitro L-arginine methyl ester (L-NAME, 1 mg/kg), or methylene blue (MTB, 1 mg/kg). Blood samples were taken before treatments on days 1, 2, and 8 for the measurement of plasma triglyceride (TG), high-density lipoprotein (HDL), low-density lipoprotein (LDL) and cholesterol levels. Results: No time-course effects in the saline-treated (control) group was observed. Nitroglycerin and L-arginine caused an increased HDL and decreased TG level on day 2 (p < 0.05). Treatment with either L-NAME or MTB increased the concentration of LDL slightly. One week treatment with either of L-NAME or MTB increased LDL and TG levels significantly (p < 0.05). Both L-arginine and NTG elevated the HDL levels and the HDL/cholesterol ratio after 1 week treatment (p < 0.05). Conclusions: These data suggest that NO donors, used routinely in cardiovascular disease therapy, may increase the levels of HDL and decrease harmful lipoprotein levels and, hence, decrease the risk of hypercholesterolemia and atherosclerosis.